2006
DOI: 10.3892/or.15.4.949
|View full text |Cite
|
Sign up to set email alerts
|

TP53 codon 72 polymorphism in radiation-associated human papillary thyroid cancer

Abstract: The study investigated an association between the germline polymorphism at TP53 codon 72 and the development of papillary thyroid cancer (PTC) following exposure to radiation from the Chernobyl accident. TP53 genotype was examined in 48 pediatric/adolescent (age at diagnosis <18 years) and 68 adult post-Chernobyl patient with PTC, 53 adult patients with sporadic PTC and 313 healthy individuals from Russian-Ukrainian population. In addition, we evaluated loss of heterozygosity for TP53 and the allele expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 34 publications
3
33
0
1
Order By: Relevance
“…This and the longlasting presence of these signatures support the susceptibility signature model. The recent finding that different TP53 alleles are associated with radiation exposure in adult PTC from Russian-Ukrainian patients (Rogounovitch et al, 2006) also supports this view. The susceptibility model, and the corollary that radiation susceptibility varies among individuals, may partly explain why only a minority of the population most exposed to radiation in Ukraine and Belarus developed PTC.…”
Section: Discussionsupporting
confidence: 66%
“…This and the longlasting presence of these signatures support the susceptibility signature model. The recent finding that different TP53 alleles are associated with radiation exposure in adult PTC from Russian-Ukrainian patients (Rogounovitch et al, 2006) also supports this view. The susceptibility model, and the corollary that radiation susceptibility varies among individuals, may partly explain why only a minority of the population most exposed to radiation in Ukraine and Belarus developed PTC.…”
Section: Discussionsupporting
confidence: 66%
“…www.endocrinology-journals.org Rogounovitch et al (2006) in Russian healthy controls is also 0.28. Thus, the effect of population admixtures in the controls in our investigation could not be completely ruled out.…”
Section: N M Akulevich Et Al: Genotypes Of Ptc Of Different Etiologymentioning
confidence: 81%
“…The study of codon 72 polymorphism in thyroid tumors from Russian and Ukrainian patients demonstrated a significantly lower frequency of wild-type homozygotes (i.e. Arg/Arg) among adults with IR-induced PTC when compared with sporadic PTC cases and general population (Rogounovitch et al 2006). Data obtained in the present work, using an independent set of samples, confirm these findings suggesting the modifying role (or as of a marker) of the TP53 Arg72Pro polymorphism in PTC developed after exposure to IR which is further supported by the absence of significant difference in genotype distributions among our two control groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations